New method for intraoperatory occlusal restauration in mandibular angle fractures treatment using two modified reduction forcepssing two modified reduction forceps - Ogoshi, José Lineu Pereira; Berardi, Rogerio Henrique; Zangrando, Denis; Horikawa, Fernando kendi; Morimoto, Susana; Shinohara, Elio Hitoshi (ARCHIVES OF HEALTH INVESTIGATION, 2020)
The treatment of mandibular angle fractures presents several possibilities for fixation methods and surgical approaches which can be intraoral or can be accessed through the skin. An important point would be intraoperative occlusal restoration. We present a method that replaces the traditional form using an erich bar and which, in our view, is a fast and effective method for intraoperative occlusal restoration. Descriptors: Inter Maxillary Fixation (IMF); Occlusion; Arch Bar Fixation. References Johnson AW. Dental occlusion ties: A rapid, safe, and non-invasive maxillo-mandibular fixation technology. Laryngoscope Investig Otolaryngol. 2017;2(4):178-83. Abbasi AJ, Parvin M. New method of arch bar fixation. Br J Oral Maxillofac Surg. 2017;55(6):631-32. Shinohara EH, Mitsuda ST, Miyagusko JM, Horikawa FK. Mandibular fracture reduction without intraoperative intermaxillary fixation: a technique using two modified reduction forceps. J Contemp Dent Pract. 2006;7(1):150-56.